COMPARISON OF MINERAL AND COAL REGULATION BASED ON MINING LAW 2009 & OMNIBUS LAW 2020 - Mufatika, Rizki; Nabilla, Nyimas Ratri; Edwin, Nabilla Putri; Purba, Kefin Kurniawan; Ramadhan, Nadzwan F. (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2024)
The purpose of this research is to criticize mining as discussed in this journal, which is still not under the Indonesian legal system and the aim of the law itself, namely to provide justice, certainty, and benefits for the community and the criticism given is based on measuring the two existing regulations in the form of similarities and differences created by these two regulations. This research also emphasizes several comparisons of previous policies with the latest policies from the government itself related to mining, as discussed in this journal, in terms of requirements, authority, and supervision. Regarding mining regulations as regulated in Law Number Four 2009, they are still unable to address developments, problems, and legal needs in mining operations discussed in this journal. Hence, a review is necessary to make this happen and provide increased added value. Or downstream. However, with the implementation of Law Number Three of 2020, many mines have also been allowed to operate without permits. The previous laws regarding the mining industry are considered valid, but in the case of the revision of the Mining Act, the implementation process of the Mining Act is also regarded as inadequate.